BUDAYA KEPEMIMPINAN ISLAMI DI INDONESIA - Salsabila Keisha Azzahra; Shindy Yosida Imansari; Mirwan Surya Perdhana (Jurnal Ilmiah Ekonomi Islam, 2022)
Indonesian leadership is strongly influenced by culture, because Indonesia has many regional cultures. Therefore, there are many regional cultures that need to be understood in determining the ideal leadership style for Indonesia. There are many leadership philosophies, some of which adopt Western models of leadership, democratic leadership and leadership based on regional philosophies. The purpose of this study was to determine the Indonesian leadership culture and the ideal leadership culture prevailing in Indonesia. This study uses a qualitative descriptive method, and the research data is secondary data related to leadership culture. The results of his research show that the leadership culture that continues to this day, especially in organizations, still considers personal factors, namely education, experience, and work skills. The ideal leadership applied in Indonesia is the leadership concept proposed by Ki Hadjar Dewantara, called tut wuri handayani, which means that a person must be able to be an example for his members, and the leader must be able to put himself in the middle. become one of his subordinates. A kind of encouragement and motivation. In addition, leaders must be able to provide encouragement so that their subordinates become better.